Office 2013 elearning kit for dummies - Wempen, Faithe (John Wiley and Sons, 2014)
Whether you're meeting Office 2013 for the first time or upgrading your knowledge from an earlier version, this value-packed eLearning kit makes it easy to learn 2013 at your own pace. This complete learning package includes a full-color printed book and an access code for one year of online self-paced training. You'll learn the basics of the Office interface, how to navigate it, and how to use the features common to all Office programs. Then you'll get detailed instructions for working with Word, Excel, PowerPoint, and Outlook